Phytoestrogens as Bioactive Compounds with Beneficial Effects for Human Health - Silva, Ana Cristina Ferrão (2017)
Phytoestrogens, also called estrogens, are bioactive compounds original from plants. They are similar in structure and functionality to the estrogenic hormones in animals. It has been documented that these compounds have several effects on the human body, namely in terms of carbohydrate, protein, lipid and mineral metabolism. Some of the most known effects of these substances are related to their roles in the women’s reproductive system. The dietary phytoestrogens are present in vegetable sources, like some herbs, grains or fruits. Their structure is similar to that of estradiol, which can act in the body both as estrogenic or antiestrogenic. They are classified into the following categories: i) isoflavones, which are essentially present in legume beans, and particularly soy beans and soy products; ii) lignans, which are part of foods rich in dietary fibre, like cereal brans, beans, legumes or oilseeds; iii) coumestans, found in various beans sucg as plit peas, pinto beanso r lima beans, and also in alfafa and clover sprouts; iv) mycoestrogens, which are produced by moulds. Phytoestrogens can be used as human health enhancers, and have many documented beneficial effects on the human body. They are reported to diminish the incidence of some types of cancer, as well as to minimize menopausal symptoms and prevent osteoporosis. Also some benefits have been associated with the ingestion of these bioactive compounds and protection against cardiovascular diseases. Hence, this chapter aims at reviewing the scientific literature about the structure of PEs, as well as their natural sources and health effects.